The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1159/000087658
|View full text |Cite
|
Sign up to set email alerts
|

Is Paradoxical Pain Induced by Sustained Opioid Exposure an Underlying Mechanism of Opioid Antinociceptive Tolerance?

Abstract: Opiates are the primary treatment for pain management in cancer patients reporting moderate to severe pain, and are being increasingly used for non-cancer chronic pain. However, prolonged administration of opiates is associated with significant problems including the development of antinociceptive tolerance, wherein higher doses of the drug are required over time to elicit the same amount of analgesia. High doses of opiates result in serious side effects such as constipation, nausea, vomiting, dizziness, somno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 166 publications
6
127
2
2
Order By: Relevance
“…Mechanisms of action proposed to be essential for the development of an increased sensitivity to pain resulting from long-term exposure to opiates include enhanced NK1 receptor transmission. 110 Experiments performed previously have shown that sustained morphine exposure increases pronociceptive agent substance P and NK1 receptor expression in the spinal dorsal horn. 110 Moreover, spinal administration of the NK1 receptor antagonist L-732,138 fully reversed thermal hypersensitivity in rats receiving sustained morphine treatment via a subcutaneous morphine-pellet implant.…”
Section: Opioid-induced Hyperalgesiamentioning
confidence: 96%
See 1 more Smart Citation
“…Mechanisms of action proposed to be essential for the development of an increased sensitivity to pain resulting from long-term exposure to opiates include enhanced NK1 receptor transmission. 110 Experiments performed previously have shown that sustained morphine exposure increases pronociceptive agent substance P and NK1 receptor expression in the spinal dorsal horn. 110 Moreover, spinal administration of the NK1 receptor antagonist L-732,138 fully reversed thermal hypersensitivity in rats receiving sustained morphine treatment via a subcutaneous morphine-pellet implant.…”
Section: Opioid-induced Hyperalgesiamentioning
confidence: 96%
“…110 Experiments performed previously have shown that sustained morphine exposure increases pronociceptive agent substance P and NK1 receptor expression in the spinal dorsal horn. 110 Moreover, spinal administration of the NK1 receptor antagonist L-732,138 fully reversed thermal hypersensitivity in rats receiving sustained morphine treatment via a subcutaneous morphine-pellet implant. 111 Interestingly, morphine-induced hyperalgesia was not observed in NK1 receptor knockout (NK1 Ϫ/Ϫ ) mice, providing evidence for a critical involvement of the NK1 receptor in the manifestation of morphine-induced hyperalgesia.…”
Section: Opioid-induced Hyperalgesiamentioning
confidence: 96%
“…A known mechanism for this phenomenon is the reduction in the responsiveness of the G-protein coupled opioid receptors (Nestler 1992) leading to either desensitization or downregulation. More recently the concept of paradoxical pain leading to analgesic tolerance has also been proposed (King, Ossipov et al 2005). …”
Section: Multivariable Regression Analysesmentioning
confidence: 99%
“…The development of opioid tolerance has also been associated with enhanced pain sensitivity such as hyperalgesia in both laboratory and clinical settings (Sjogren et al, 1993;Mao et al, 1994Mao et al, , 2002Vanderah et al, 2000Vanderah et al, , 2001. There is emerging evidence suggesting that opioid tolerance and pathological pain may share common cellular mechanisms (Mao et al, 1995a;Mayer et al, 1999), and the abnormal pain elicited by opioids is a critical factor in the behavioral manifestation of opioid tolerance because the same manipulations that block abnormal pain also block opioid tolerance (King et al, 2005b;Ossipov et al, 2005). Despite considerable progress, the molecular and cellular mechanisms mediating morphine tolerance are not yet completely understood.…”
Section: Introductionmentioning
confidence: 99%